2023
DOI: 10.3390/cancers15153829
|View full text |Cite
|
Sign up to set email alerts
|

A Radiomics-Clinical Model Predicts Overall Survival of Non-Small Cell Lung Cancer Patients Treated with Immunotherapy: A Multicenter Study

Abstract: Background: Immune checkpoint inhibitors (ICIs) are a great breakthrough in cancer treatments and provide improved long-term survival in a subset of non-small cell lung cancer (NSCLC) patients. However, prognostic and predictive biomarkers of immunotherapy still remain an unmet clinical need. In this work, we aim to leverage imaging data and clinical variables to develop survival risk models among advanced NSCLC patients treated with immunotherapy. Methods: This retrospective study includes a total of 385 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The studies utilized diverse AI/ML techniques, including deep learning (DL), artificial neural networks (ANNs), support vector machines (SVMs), random forests (RFs), and gradient boosting methods (e.g., XGBoost). These algorithms were applied to various data modalities, such as medical imaging (computed tomography (CT), positron emission tomography (PET)), genomic data (TMB, gene expression), clinical variables (performance status, blood counts), and immunohistochemical markers (PD-L1, TILs) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The studies employed various performance metrics to evaluate the predictive accuracy of their AI/ML models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies utilized diverse AI/ML techniques, including deep learning (DL), artificial neural networks (ANNs), support vector machines (SVMs), random forests (RFs), and gradient boosting methods (e.g., XGBoost). These algorithms were applied to various data modalities, such as medical imaging (computed tomography (CT), positron emission tomography (PET)), genomic data (TMB, gene expression), clinical variables (performance status, blood counts), and immunohistochemical markers (PD-L1, TILs) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The studies employed various performance metrics to evaluate the predictive accuracy of their AI/ML models.…”
Section: Discussionmentioning
confidence: 99%
“…. Similarly,Yolchuyeva et al (2023Yolchuyeva et al ( , 2024 developed ML models incorporating cytokine profiles and clinical variables that effectively predicted OS and PFS in patients receiving anti-PD-1/PD-L1 immunotherapy[9,10].Vanguri et al (2022) andHe et al (2022) utilized multimodal data, including CT images, genomic features, and clinical variables, to build ML models that outperformed single biomarkers like TMB in predicting immunotherapy response[12,13]. employed eXplainable AI (XAI) and ML techniques to develop a model that accurately predicted disease control rate, OS, and time to treatment failure, while also identifying influential features such as neutrophil-to-lymphocyte ratio and PD-L1 expression[14,17].…”
mentioning
confidence: 99%
“…The recent advent of radiomics through quantitative image analysis has been gaining interest in oncology as a novel strategy for predicting treatment response. 33 , 34 , 35 , 36 Nevertheless, the development of imaging-based signatures that can be robust and generalizable across academic centers has been a bottleneck to adopt radiomics in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics can be quantified using well-defined mathematical equations to obtain the underlying characteristics of the disease through image intensity, shape, or texture, thereby overcoming the subjective nature of image interpretation [10]. Many studies, including our recent works, have investigated and reported on the added clinical value of radiomics features to predict various clinical and biological outcomes in immunotherapy-treated patients, such as overall survival, progression-free survival, tumor histology, and genetic profiling, among other endpoints [9,[11][12][13]. On the other hand, the rapidly expanding field of pathomics aims to investigate the micro-scale patterns from the digitized histopathology slides, or whole slide imaging (WSI), in a high-throughput manner [4,14].…”
Section: Introductionmentioning
confidence: 99%